Analysis of Learning Styles of Class X PPLG B Students at Surakarta State Vocational School Based on Bobby Deporter's Theory - Syafi'uddin, Mochkammad Tabah; Efendi, Agus; Pramono, Sidik (IJIE (Indonesian Journal of Informatics Education), 2023)
The findings of observations at a school, specifically the learning preferences of the pupils in class X PPLG B at SMK N Surakarta, served as the impetus for this investigation. The goal of this study is to examine how students' learning styles in class X PPLG B at SMK N Surakarta are described in terms of the Bobby DePorter hypothesis. A qualitative methodology is employed with a descriptive-analytical method for the investigation. Ten pupils from class X PPLG B and two PPLG field teachers participated in this study. The approach of purposive sampling was employed in the selection of participants. Data for the study was gathered via interviews and observation. Ten participants—students enrolled in a basic computer assembly course at one of Surakarta's public vocational schools—were directly observed during the observation. When the students were working on their computer assembly subject practicum, the observation procedure lasted for around four hours of class time. Two participants were interviewed face-to-face, namely instructors of the core subject of the program of expertise at one of Surakarta's public vocational schools. The interview procedure with the teacher was conducted for roughly 20 minutes with 6 questions about the learning styles of pupils in class X PPLG B at SMK N Surakarta. There is a wide range of learning styles in class X PPLG B, including auditory, kinesthetic, and visual learning styles, according to the findings of the interview with the teacher. This is also evident in the observational data, which shows that each student uses a particular learning style based on their unique set of traits.